2020
DOI: 10.3390/atmos11101044
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Climate Variations at Four Meteorological Stations on Remote Islands in the Croatian Part of the Adriatic Sea

Abstract: The Mediterranean region is one of the regions in the world that is most vulnerable to the impact of imminent climate change. In particular, climate change has an adverse effect on both the ecosystem and socioeconomic system, influencing water availability for both human and environmental purposes. The most endangered water resources are along the coasts and on islands since they have relatively small volumes and are intensively exploited. We analyzed the time series of air temperature and precipitation measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 19 publications
3
12
0
Order By: Relevance
“…This presumption suggests that an early warning system for the Korita extraction site should be placed between Korita and the town of Vis (possibly also north of Korita), and its installation should be preceded by additional geophysical research, e.g., electrical tomography [71]. Such a system would be more than advisable given the increasing irregularity in the precipitation regime, which is similar to globally observed climate change trends and their reflection on the Adriatic region [23,72]. Water balance calculations performed by Terzić [16] suggested that < 1% of the annually infiltrated water discharges from all registered spring localities and zones, whereas > 99% of the total discharge occurs via diffuse outflow zones in the northern and southern coast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This presumption suggests that an early warning system for the Korita extraction site should be placed between Korita and the town of Vis (possibly also north of Korita), and its installation should be preceded by additional geophysical research, e.g., electrical tomography [71]. Such a system would be more than advisable given the increasing irregularity in the precipitation regime, which is similar to globally observed climate change trends and their reflection on the Adriatic region [23,72]. Water balance calculations performed by Terzić [16] suggested that < 1% of the annually infiltrated water discharges from all registered spring localities and zones, whereas > 99% of the total discharge occurs via diffuse outflow zones in the northern and southern coast.…”
Section: Discussionmentioning
confidence: 99%
“…Air temperatures are highest during July and August and lowest in January [22]. In a newer study [23], there was a bulk analysis of climate variations on Komiža station, which is representative of the island of Vis (neglecting differences within the island, as no other stations were analyzed). The absolute minimum and maximum annual air temperatures were −1.12 °C and 35.01 °C, respectively, and the mean annual air temperature was 16.71 °C, while the average annual precipitation for the station was 792 mm.…”
Section: Physical Setting (Geography Morphology Geology and Hydrogeology)mentioning
confidence: 99%
“…Finally, the rescaled adjusted partial sums (RAPS) were used to detect and quantify the trends, shifts, data clustering, irregular fluctuations, and periodicities in the record in timeseries [42]. The specific approach was successfully applied in the analysis of hydrological, meteorological, and water quality indicators [43][44][45][46][47][48]. The RAPS method is based on the analysis of the time distribution of the outflow of the summary deviation curve and is expressed as [49]:…”
Section: Time Series Statistical Analysismentioning
confidence: 99%
“…This area has the climate type Csa (Mediterranean climate with a hot summer) [4]. The climatological characteristics of the area are visible from the data of the local Biševo meteorological station (a precipitation station on Biševo) and the stations on the surrounding islands, observed in the period 1958-2018 [5]. The mean average annual air temperature on the surrounding islands ranges from 15.80-16.71 • C, and the mean total annual precipitation on Biševo is 617 mm.…”
Section: Geographical and Geological Settingmentioning
confidence: 99%